Drip application of chlorantraniliprole effectively controls invasive Spodoptera frugiperda (Lepidoptera: Noctuidae) and its distribution in maize in China. (May 2021) - Li, Xianjia; Jiang, Hui; Wu, Jiyingzi; Zheng, Feng; Xu, Kaijie; Lin, Yigang; Zhang, Zhixiang; Xu, Hanhong
Abstract: Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is one of the most important agricultural pests in the world and a major invasive pest in China. It invaded China in December 2018 and seriously affected the output and quality of maize. At present, the most common prevention and control technology in China is artificial or drone spray. However, the drift of spray droplets seriously affects the safety of sprayers and the environment, and also affects natural enemies and insects. The control effect of chlorantraniliprole on S. frugiperda under drip irrigation and its distribution and transmission in maize were studied. The results showed that 1200 g a.i. ha −1 chlorantraniliprole through drip irrigation effectively controlled S. frugiperda for 40 days, and its control effect was longer than that of artificial or drone spray. Chlorantraniliprole had a very strong transport capacity from stems to leaves and concentrated in the upper leaves of maize which were the main damage of S. frugiperda . At harvest, chlorantraniliprole was not detected in any part of maize plant. These results indicated that chlorantraniliprole can control the invasive pest S. frugiperda more efficiently, long-term, and accurately through drip irrigation. Graphical abstract: Image 1 Highlights: Chlorantraniliprole applied via drip irrigation effectively controls invasive Spodoptera frugiperda in China. Through drip irrigation of chlorantraniliprole, the medicine is concentrated in the upper leaves of maize. Drip irrigation has a longer control effect, and is convenient, and has a small negative impact on the environment. Drip irrigation of chlorantraniliprole can be promoted in non-arid areas due to its excellent resistance to rain erosion.